2003
DOI: 10.1016/s0378-1097(03)00394-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the non-photosynthetic green micro-algal genus Prototheca (Trebouxiophyceae, Chlorophyta) and related taxa inferred from SSU and LSU ribosomal DNA partial sequence data

Abstract: All five species in the heterotrophic micro-algal genus Prototheca and their relatives were compared for the extent of nucleotide divergence in the nuclear small-subunit (SSU) and in the 5' end of large-subunit (LSU) ribosomal RNA genes (rDNAs). Phylogenetic analysis based on combined SSU and LSU rDNA sequence alignment was implemented with the neighbor-joining, the maximum-parsimony, and the maximum-likelihood methods. The relationships among the species of Prototheca based on this data set were largely conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
39
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 24 publications
9
39
0
Order By: Relevance
“…Hegewald and Kneifel (1982) reported that differences in the pattern of the polyamines within the genus Chlorella led to separation of two groups: those characterized by the near absence of norspermidine and those by high concentration of norspermidine. However, it has been shown that phylogenetically heterogeneous Chlorella species distribute in different clusters in the Trebouxiophyceae and Chlorophyceae (Ali et al, 2001;NCBI home page, 2004;Ueno et al, 2003). In the present study, C. vulgaris, C. kessleri and C. sorokiniana belonging to authentic genera Chlorella as well as "C. saccharophila" and "C. ellipsoidea" located in another cluster of Trebouxiophyceae were almost entirely lacking in norspermidine.…”
mentioning
confidence: 40%
See 2 more Smart Citations
“…Hegewald and Kneifel (1982) reported that differences in the pattern of the polyamines within the genus Chlorella led to separation of two groups: those characterized by the near absence of norspermidine and those by high concentration of norspermidine. However, it has been shown that phylogenetically heterogeneous Chlorella species distribute in different clusters in the Trebouxiophyceae and Chlorophyceae (Ali et al, 2001;NCBI home page, 2004;Ueno et al, 2003). In the present study, C. vulgaris, C. kessleri and C. sorokiniana belonging to authentic genera Chlorella as well as "C. saccharophila" and "C. ellipsoidea" located in another cluster of Trebouxiophyceae were almost entirely lacking in norspermidine.…”
mentioning
confidence: 40%
“…are known to be pathogenic to vertebrates (Galan et al, 1997;Mohabeer et al, 1997). Another non-photosynthetic unicellular green algal group consisting of the Polytoma and Polytomella species belongs to Chlorophyceae (Nedelcu, 2001;Tartar et al, 2003;Ueno et al, 2003). They have degenerate chloroplasts and grow heterotrophically in the dark whereas other green algae ordinarily grow phototrophically in the light.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The non-photosynthetic, parasitic Prototheca and Helicosporidium are also included in the Chlorellales based on nuclear and chloroplast gene data (Huss & Sogin, 1990;Tartar et al, 2003;Ueno et al, 2003;de Koning et al, 2005;Ueno et al, 2005). Although plastids are not apparent in Helicosporidium cells, molecular evidence indicates that it maintains a functional plastid genome (Tartar et al, 2003;de Koning & Keeling, 2004;Tartar & Boucias, 2004;de Koning & Keeling, 2006).…”
Section: Trebouxiophyceaementioning
confidence: 99%
“…Specific oligonucleotides: The P. zopfii-specific primers 18PZF1 and 18PZR1 were generated on the basis of the alignment of the small subunit ribosomal DNA (SSU rDNA) base sequences of the genera Chlorella and Prototheca obtained from DDBJ/EMBL/ GenBank (25,26,45). The TaqMan } MGB probe PZP1 (nucleotides 378-395 of the SSU rDNA sequence, DDBJ/EMBL/GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%